Efektivitas Pemakaian Mesin Magic Sugar Cane Terhadap Penurunan Kualitas Nira pada Sistem Tebang Angkut - Retno Muji Rahayu; Warkoyo; Noor Harini; Rista Anggriani (Fakultas Teknologi Pertanian, Universitas Udayana Gedung GA, Fakultas Teknologi Pertanian, Universitas Udayana Jl. Raya Bukit Jimbaran, Jimbaran, Kuta Selatan, Bali Telp/Fax: (0361) 701801, 2022)
The Sugarcane plantations have a role in the development of agriculture in Indonesia. Sugarcane is needed by industry as raw material for making sugar. It is one of the nine main ingredients on making sugar. National sugar production has decreased due to the delay in sugarcane milling (down time). The milling delay of up to three days can reduce the quality of the nira in terms of the increasing in °Brix, decreasing in pH, increasing in reducing sugar content in °Brix. In addition, it can also reduce the nature of purity which can affect the amount of sugar yield produced. The Magic Machine Sugarcane is a sugarcane harvesting machine to produce nira. The purpose the Magic Machine Sugar Cane is an effort to maintain the physical and chemical quality of the nira in the cutdown system. The design method of Magic machine sugarcane starts from drafting the concept, designing, and testing. The test parameters used were total sugar, viscosity, TSS, total acid and pH. The results of the Magic Machine Sugar Cane is designed with a height of 1.85 meters and a width of 1.65 meters and a length of 3.75 meters consisting of diesel components, cutting blades, cane carriers, cane cutters, wheels, roller mills, filters, handles, frame body and equipped with a storage tube with the principle of maintaining the nira temperature to 5 ºC. The Storage of nira at 5 ºC minimize the loss of total sugar value, viscosity, TSS value from 16 °Brix to 18 °Brix, total acid value in the range of 0.045%-0.055% and pH 5.0-6.0. So that the Magic Machine Sugar Cane is effective in maintaining the physical and chemical quality of the nira during the cutdown system.